Surgical outcomes of segmental bronchial sleeve resection in central non‐small cell lung cancer. Issue 5 (21st March 2020) - Qu, Rirong; Ping, Wei; Hao, Zhipeng; Cai, Yixin; Zhang, Ni; Fu, Xiangning
Abstract : Background: The purpose of this study was to present the clinical and surgical results in patients who underwent segmental bronchial sleeve reconstruction. Methods: The clinical and pathological data of 16 patients with central non‐small cell lung cancer (NSCLC) who underwent segmental bronchial sleeve resection from April 2015 to May 2019 were retrospectively analyzed. Results: According to the type of segmental bronchial reconstruction, procedures were divided into four types: right upper S6 sleeve lobectomy in three cases (type A); left lower lingular sleeve lobectomy in 10 cases (type B); left upper S6 sleeve lobectomy in two cases (type C); and left lower propriolateral superior sleeve lobectomy in one case (type D). A total of three patients (18.75%) experienced anastomotic complications, including two with anastomotic stenosis and one with anastomotic fistula. All patients achieved R0 resection. Apart from one patient who died of acute lung infection after surgery, the rest were successfully discharged. The average follow‐up time was 28 months, and the overall survival rates of patients at one, two, and three years were 80.0%, 53.3%, and 40.0%, respectively. Conclusions: Segmental bronchial sleeve resection is complex in technique and may have an increased risk of complications compared to a standard sleeve resection, but it is an effective and safe procedure, especially for selected patients with central lung cancer.